Desain Eksperimental: Pengaruh Pengkomunikasian Sejarah CSR pada Persepsi Konsumen dalam Mengatasi Publisitas Negatif: Consumer Support Sebagai Variabel Covariate - Edo Wijaya Alfianus; Nonie Magdalena (Universitas Kristen Maranatha, 2012)
The negative publicity is a threat that cannot be avoid and predicted by the company. When the negative publicity to attack a company then directly to damage a company’s reputation. The company needs strategy to react quickly andright in the face of the negative publicity. CSR activities can becomes strategy that effective to fight the negative publicity. This research goal seeking to test and to analysis influence the communicating of CSR history on consumer perceptions inresisting the negative publicity and consumer support can be used as a variable covariate. The kind of research is design experimental using 2 (two) scenario as treatments. A method of data analysis use Analysis of Covariance (ANCOVA). As awhole research showed that the presence of influence the communicating of CSR history on consumer perceptions, and consumer support are proven can increase influence on consumer perceptions. This research also proves that thecommunicating of long CSR history can be a means of communication that is effective to counter the negative publicity.